2015
DOI: 10.1111/mono.v80.3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Among the earliest volumes of this Monograph series was a report by Lester Sontag and colleagues, of the esteemed Fels Institute, on the heart rate of the human fetus as an expression of the developing nervous system. Here, some 75 years later, we commemorate this work and provide historical and contemporary context on knowledge regarding fetal development, as well as results from our own research. These are based on synchronized monitoring of maternal and fetal parameters assessed between 24 and 36 weeks gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 308 publications
(465 reference statements)
3
36
1
Order By: Relevance
“…We did not find that GA was correlated with FHR and FHRV, perhaps due to low power and the small range for gestational age (36-39 weeks). Despite this, our results suggest that males exhibit the more mature pattern as they have lower FHR and higher FHRV than females (DiPietro et al, 2015). Similarly, FHRV was reported to be less complex for near-term male fetuses compared to female fetuses, indicating a more mature nervous system that functions more autonomously (Bernardes et al, 2008).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…We did not find that GA was correlated with FHR and FHRV, perhaps due to low power and the small range for gestational age (36-39 weeks). Despite this, our results suggest that males exhibit the more mature pattern as they have lower FHR and higher FHRV than females (DiPietro et al, 2015). Similarly, FHRV was reported to be less complex for near-term male fetuses compared to female fetuses, indicating a more mature nervous system that functions more autonomously (Bernardes et al, 2008).…”
Section: Discussioncontrasting
confidence: 58%
“…In a larger study, DiPietro, Costigan, & Voegtline (2015) collected data from 740 fetuses and found that in the late term fetus, males show a more mature pattern of autonomic function than females.…”
Section: Introductionmentioning
confidence: 99%
“…A primary advantage to studying neurobehavioral development in utero is that associations between maternal psychological distress and developmental outcomes can be examined prior to postpartum influences. Measures of fetal brain and neurobehavioral development are more proximal and likely more accurate indicators of fetal exposures (DiPietro, Costigan, & Voegtline, 2015; Sandman, 2015). Very recent advances in fetal functional magnetic resonance imaging have enabled direct observation of brain development during the prenatal period (Thomason et al, 2018; van den Heuvel & Thomason, 2016).…”
mentioning
confidence: 99%
“…Very recent advances in fetal functional magnetic resonance imaging have enabled direct observation of brain development during the prenatal period (Thomason et al, 2018; van den Heuvel & Thomason, 2016). However, there is a long-standing tradition of assessment of fetal behavior as a noninvasive method of measuring neurodevelopment (see DiPietro et al, 2015). Fetal heart rate (FHR) and fetal movement parameters are established indices of central and autonomic nervous system maturation and function which demonstrate continuity with postnatal outcomes (DiPietro et al, 2015, 2010; Nijhuis, Swaab, Heuser, Brosens, & Eskes, 2003; Sandman, 2015).…”
mentioning
confidence: 99%
“…In just 266 days, a single fertilized cell develops into a sentient human newborn infant” (DiPietro, 2010). Further, “there is no other period in development in which the proximal environment is so physiologically entangled” with the offspring (DiPietro, Costigan, & Voegtline, 2015). Ongoing improvements in ultrasound technology and fetal monitoring have allowed understanding of fetal development to progress from delineating structural and organ development to assessing patterns of fetal movements and fetal heart rate (FHR) to elucidating fetal state and neurobehavior (DiPietro et al, 2010; Groome, Bentz, & Singh, 1995; Nijhuis, Martin, & Prechtl, 1984; Nijhuis, Prechtl, Martin, & Bots, 1982).…”
mentioning
confidence: 99%